Internet Use and Decision-Making Processes among Pregnant Women: A Cross-Sectional Study - Balmumcu, Ayça; Çetinkaya Ak, Endam; Uçan Yamaç, Sabriye (Makara Journal of Health Research, 2026)
Background: The coronavirus disease 2019 (COVID-19) pandemic restricted access to in-person health services, especially in rural areas. This increased reliance on the internet for health information and decision-making was particularly notable among pregnant women. This study aimed to investigate the role of internet use in decision-making among pregnant women. Methods: This analytical, cross-sectional study examined 384 pregnant women living in a rural district of Turkey who attended family health centers for prenatal care. Data were collected using the Internet Decision-Making Scale in Pregnancy and a questionnaire assessing internet use patterns during the pandemic. Results: Pregnant women demonstrated high levels of internet-based decision-making regarding pregnancy-related issues. Time spent online increased during the COVID-19 pandemic, and most participants reported trusting the pregnancy-related information they obtained online. Higher age was associated with higher Internet-based decision-making scores. Conclusions: The internet plays a crucial role in influencing pregnant women’s decisions during periods of limited access to healthcare services, especially in rural areas. Understanding how and when women use the internet for these decisions is essential for safeguarding maternal and infant health and for developing safe, evidence-based digital support strategies.